The Model of Entrepreneurial Skill and Business Performance at Coffee Cafe in Bandung - Tondo, Anthon S.; Saptari, Hendarsyah A. (Dinasti Publisher, 2024)
This paper aims to explore the relationship between entrepreneurial skills and business performance at coffee cafés in Bandung. The study focuses on identifying key entrepreneurial competencies, such as creativity, leadership, financial management, and customer relationship management, that contribute to the success of coffee businesses. Data was collected through surveys and interviews with café owners across Bandung, and the results were analyzed to determine which skills have the most significant impact on business performance. The findings reveal that entrepreneurial skills, particularly in innovation and customer management, play a crucial role in improving business outcomes. These insights provide valuable guidance for coffee café entrepreneurs seeking to enhance their business performance in a competitive market.